Radical Scavenging Activities of Some Vitis vinifera Varieties Grown in Malatya (Turkey) and Their Preventive Effects on the Formation Lipid Peroxidation in Unsaturated Fatty Acids Mediated - Ozsahin, Ayse Dilek; Yilmaz, Okkes; Tuzcu, Mehmet; Kirecci, Oguz Ayhan; Guvenc, Mehmet (Asian Journal of Chemistry, 2010)
This study examined the phytochemical characteristics of five samples of Vitis vinifera grown in the Malatya region of Turkey and investigated their impacts on human health by determining their antioxidant activities in vitro. The present research includes five native grape varieties (white: Tahanebi, Sam and Kureys; red: Kohnu; black: Banazi. Karasi). Antioxidative activities of the grape extracts were determined with the following modifications. The free radical scavenging effect in extracts was assessed by the decolouration of a methanolic solution of DPPH. Lipid peroxidation level was found to be significantly high in the Fenton reagent (FR) containing group when compared to the control group (p < 0.0001). However, lipid peroxidation level decreased significantly in the groups to which grape extracts were added (p < 0.0001). According to DPPH results, all grape samples showed effective antioxidant activity in different concentrations and these activities were observed to change in parallel with the increase in flavonoid concentration. The results indicate that the grape fruit extracts decrease lipid peroxidation level in the Fenton reagent environment and have scavenging effect on the DPPH center dot depending on grape varieties.
Keywords: Grape; alpha,alpha-Diphenyl-beta-picrylhydrazyl (DPPH); Lipid peroxidation; Flavonoids; Antioxidant capacity